2014
DOI: 10.1128/mcb.00799-13
|View full text |Cite|
|
Sign up to set email alerts
|

Beta-Like Importins Mediate the Nuclear Translocation of Mitogen-Activated Protein Kinases

Abstract: The rapid nuclear translocation of signaling proteins upon stimulation is important for the regulation of de novo gene expression. We have studied the stimulated nuclear shuttling of c-Jun N-terminal kinase (JNK) and p38 mitogen-activated protein kinases (MAPKs) and found that they translocate into the nucleus in a Ran-dependent, but NLS-or NTS-independent, manner, unrelated to their catalytic activity. We show that this translocation involves three ␤-like importins, importins 3, 7, and 9 (Imp3/ 7/9). Knockdow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 53 publications
0
36
0
Order By: Relevance
“…Although a phosphorylation-based NLS has been proposed for ERK2 (137), the implicated site is not functional in JNK or the p38 kinases (138). The ERK2 NLS is also problematic due to structural reasons: the proposed site is rigidly folded and does not appear to be available for intramolecular autophosphorylation.…”
Section: Jnk Nucleo-cytoplasmic Traffickingmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a phosphorylation-based NLS has been proposed for ERK2 (137), the implicated site is not functional in JNK or the p38 kinases (138). The ERK2 NLS is also problematic due to structural reasons: the proposed site is rigidly folded and does not appear to be available for intramolecular autophosphorylation.…”
Section: Jnk Nucleo-cytoplasmic Traffickingmentioning
confidence: 99%
“…Regardless, nuclear translocation of both active and inactive MAPKs may also be mediated by several ␤-importins. For example, importin-3, importin-7, and importin-9 have all been implicated in mediating JNK nuclear entry (138). The use of these different importin systems could thus provide multiple nuclear entry modes for other MAPKs (142) as well as the JNKs.…”
Section: Jnk Nucleo-cytoplasmic Traffickingmentioning
confidence: 99%
“…In addition, we have recently shown that the mechanism of translocation of ERK1/2 is distinct from the other mitogenactivated protein kinases (MAPKs) JNK1/2 and p38a/b (ref. 23).…”
mentioning
confidence: 99%
“…S246 of ERK2 is the homologous residue of T241 of p38␤ and is generally very well conserved in all MAPKs (see below). However, in p38␤, T241 phosphorylation has no role in nuclear translocation (46) but rather has a role in the regulation of autophosphorylation activity. In addition to T241, we have identified two more previously unnoticed sites, S143 and S261.…”
Section: Discussionmentioning
confidence: 99%